Branched-Chain Amino Acids (BCAAs): Revisiting Their Role in Sport and Health - Aleksandra Kajtel; Anna Skowronek; Martyna Piekarska; Katarzyna Dąbek; Michał Ochwat; Maria Sudoł; Gabriela Mierzwa (Journal of Education, Health and Sport)
Branched-chain amino acids (BCAAs), particularly leucine, are essential amino acids recognized for their significant roles in muscle protein synthesis, reducing muscle catabolism, and supporting metabolic health. This review explores the biochemistry, metabolism, and signaling pathways of BCAAs, emphasizing their potential therapeutic applications in conditions like sarcopenia, liver cirrhosis, and cachexia. BCAA metabolism primarily occurs in skeletal muscle and liver, with leucine activating key signaling pathways like mTORC1, promoting muscle growth and reducing protein breakdown. Clinical studies demonstrate the potential benefits of BCAA supplementation, particularly when combined with resistance exercise, in improving muscle quality and functional outcomes. However, effects on broader physical performance markers, insulin sensitivity, and metabolic profiles remain inconsistent. Safety data indicates leucine is well-tolerated at dosages up to 0.53 g/kg/day, but optimal dosages and timing require further study. Despite promising findings, the efficacy of BCAA supplementation is context-dependent, highlighting the need for longer trials and research targeting specific populations, including the elderly and those with chronic illnesses. Future research should focus on personalized protocols, the safety of long-term use, and combining BCAA supplementation with other interventions to maximize therapeutic potential. This article aims to revisit the biochemistry, therapeutic applications, and safety of BCAA supplementation, highlighting its potential in muscle preservation and metabolic health while identifying gaps for future research.